High dose dual antibiotic loaded cement for hip hemiarthroplasty (WHiTE 8): a randomised controlled trial - Agni, NR; Costa, M; Achten, J; Peckham, N; Dutton, S; Png, M; Reed, MR (Elsevier, 2023)
Background Hip fracture is the most common injury requiring treatment in hospital. Controversy exists regarding the use of antibiotic loaded bone cement in hip fractures treated with hemiarthroplasty. We aimed to compare the rate of deep surgical site infection in patients receiving high-dose dual-antibiotic loaded cement versus standard care single-antibiotic loaded cement. Methods We included people aged 60 years and older with a hip fracture attending 26 UK hospitals in this randomised superiority trial. Participants undergoing cemented hemiarthroplasty were randomly allocated in a 1:1 ratio to either a standard care single-antibiotic loaded cement or high-dose dual-antibiotic loaded cement. Participants and outcome assessors were masked to the treatment allocation. The primary outcome was deep surgical site infection at 90 days post-randomisation as defined by the US Centers for Disease Control and Prevention in an as-randomised population of consenting participants with available data at 120 days. Secondary outcomes were quality of life, mortality, antibiotic use, mobility, and residential status at day 120. The trial is registered with ISRCTN15606075. Findings Between Aug 17, 2018, and Aug 5, 2021, 4936 participants were randomly assigned to either standard care single-antibiotic loaded cement (2453 participants) or high-dose dual-antibiotic loaded cement (2483 participants). 38 (1·7%) of 2183 participants with follow-up data in the single-antibiotic loaded cement group had a deep surgical site infection by 90 days post-randomisation, as did 27 (1·2%) of 2214 participants in the high-dose dual-antibiotic loaded cement group (adjusted odds ratio 1·43; 95% CI 0·87–2·35; p=0·16). Interpretation In this trial, the use of high-dose dual-antibiotic loaded cement did not reduce the rate of deep surgical site deep infection among people aged 60 years or older receiving a hemiarthroplasty for intracapsular fracture of the hip. Funding Heraeus Medical. Supported by the UK National Institute for Health and Care Research Oxford Biomedical Research Centre.